Experimental research on microstructure characteristics and mechanical performance of interfaces between concrete layers - Shen, Jiarong; Wang, Shouguang; Qian, Peng; Liu, Yang; Chen, Yulong (Frontiers in Materials, 2025)
In this study, the effects of the interval time between successive layers on the microstructures and macro performances of overlay transition zones (OTZs) in conventional concrete and roller-compacted concrete (RCC) are investigated. First, the fluorescent epoxy impregnation method is used to obtain microstructure images of their OTZs. Microcrack skeletons are distinguished and extracted using the traditional digital image recognition algorithm. Thus, the effects of the interval time on OTZ microstructures can be better evaluated. Then, splitting tensile strength tests are conducted to study the effects of the interval time on the macromechanical properties and failure surfaces of the OTZs. Accordingly, the relationships between the microstructural characteristics and macromechanical properties of the OTZs are established. Finally, the differences in the microstructural characteristics of the conventional concrete and the RCC are examined. The effects of their microstructures on their macro performance and failure surfaces are compared and analyzed. Consequently, this study provides experimental and theoretical references for constructing concrete dams.